Bilateral Thalamic Glioma –A Rare Tumour (Journal of Nobel Medical College, 2014)
We report a case of 48-year old woman who presented with dementia, progressive mental decline, personality change, paresis of the right lower extremity, and gait ataxia. Magnetic resonance imaging (MRI) T1-weighted image revealed bilateral thalamic swelling with homogenous low signal intensity and mild contrast enhancement with gadolinium. The T2- weighted image showed high intensity lesions in the bilateral thalamus, septum pellucidum and fornix. A CT-guided stereotactic biopsy of the lesion revealed fibrillary astrocytoma grade III as per WHO classification. Bilateral thalamic gliomas are very rare tumours and when present may resemble other benign diseases having similar clinical presentations DOI: http://dx.doi.org/10.3126/jonmc.v3i1.10059   Journal of Nobel Medical College Vol.3(1) 2014; 71-73